Blockade of Glycine Transporter (GlyT) 2, but Not GlyT1, Ameliorates Dynamic and Static Mechanical Allodynia in Mice With Herpetic or Postherpetic Pain - Yukitoshi Nishikawa; Atsushi Sasaki; Yasushi Kuraishi (Elsevier, 2010)
Glycine is an inhibitory neurotransmitter in the spinal dorsal horn and its extracellular concentration is regulated by glial glycine transporter (GlyT) 1 and neuronal GlyT2. This study was conducted to elucidate the effects of intrathecal injections of GlyT1 and GlyT2 inhibitors on two distinct types of mechanical allodynia, dynamic and static allodynia, in mice with herpetic or postherpetic pain. The GlyT2 inhibitor ALX1393, but not the GlyT1 inhibitor sarcosine, suppressed dynamic and static allodynia at the herpetic and postherpetic stages. Intrathecal ALX1393 suppressed dynamic allodynia induced by intrathecal strychnine and N-methyl-d-aspartate (NMDA). Intrathecal sarcosine suppressed dynamic allodynia induced by intrathecal strychnine, but not NMDA. Expression level of GlyT1, but not GlyT2, mRNA in the lumbar dorsal horn was decreased at the herpetic and postherpetic stages. Glycine receptor α1-subunit mRNA was decreased in the lumbar dorsal horn at the herpetic, but not postherpetic stage, without alteration in α3-subunit mRNA. The results suggest that GlyT2 is a potential target for treatment of dynamic and static allodynia in patients with herpes zoster and postherpetic neuralgia. The lack of efficacy of GlyT1 inhibitor may be explained by activation of NMDA receptors and the down-regulation of GlyT1 in the lumbar dorsal horn. Keywords:: dynamic allodynia, herpetic pain, postherpetic neuralgia, glycine transporter, glycine receptor